Thematic Dictionary of Russian Collocations for Educational Purposes: Definition and Challenges in Dictionary Compilation - A. V. Khrunenkova (Научный диалог, 2023)
The relevance of the article is determined by the fact that the selection of stable collocations for teaching foreign language learners is a multi-stage and complex process. It is noted that there is still no consensus regarding the requirements for selecting units and the volume of phraseological minimum. The novelty of the study lies in an attempt to distinguish between the concepts of “phraseological minimum” and “educational dictionary of stable collocations”. In addition, the research task is to develop criteria for selecting stable collocations for inclusion in an educational dictionary. The author’s task was to form an educational dictionary consisting of thematic sections, where the name of each section corresponds to the theme of the module in the program for teaching Russian as a foreign language. To achieve this goal, the author reviews existing scientific literature, educational dictionaries, and lexical minimums. The author analyzes textbooks on phraseology and speaking for levels B1+ — C1. The results of a survey conducted among native Russian speakers are presented in order to clarify the understanding of selected units, and an analysis of the contexts in which they are used is performed. In the final stage, a list of stable collocations on the topic of “Education” is proposed, which includes phraseological neologisms for the first time.